2016
DOI: 10.46745/ilma.jbs.2016.12.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure, Board Size, Board Composition and Dividend Policy: New Evidence From Two Emerging Markets

Abstract: Good corporate governance practices build equilibrium between management and shareholders and eliminate agency problems, as results managers pursue a suboptimal dividend policy. The aim of this study is to examine the potential relationship between ownership structure, board size, board composition, CEO duality and dividend policy of 176 listed firms at KSE and 280 listed firms at BSI from 2010-2015. We used pooled OLS regression test to analyze the association between corporate governance determinants and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
2
9
0
1
Order By: Relevance
“…Rahman (2002) stipulates that dividend smoothing is negatively related to a country's ownership level as well as firm concentration. In another similar study, Shahid et al (2016) confirm these findings in the Pakistani and Indian contexts. They find a negative link between ownership concentration and DDP.…”
Section: Ownership Concentration and Dividend Distribution Policysupporting
confidence: 74%
See 2 more Smart Citations
“…Rahman (2002) stipulates that dividend smoothing is negatively related to a country's ownership level as well as firm concentration. In another similar study, Shahid et al (2016) confirm these findings in the Pakistani and Indian contexts. They find a negative link between ownership concentration and DDP.…”
Section: Ownership Concentration and Dividend Distribution Policysupporting
confidence: 74%
“…Based on this analysis, it is expected that boards chaired by the CEO will be less effective in limiting managerial discretion, particularly with respect to the DDP. To this end, in order to overcome the poor governance practices adopted by the management team members, other authors (e.g., Shahid et al 2016;Sumail 2018;Tahir et al 2020a) stipulate that the duality of functions would favor the distribution of dividends for controlling shareholders in firms with concentrated ownership. In this sense, Taleb and Ben Lahouel (2020) recently found that Tunisian firms with a CEO in charge tend to pursue a generous DDP.…”
Section: Ceo Duality and Dividend Distribution Policymentioning
confidence: 99%
See 1 more Smart Citation
“…The findings show that sample firms are more likely to pay dividends when they have a higher ownership concentration or when the largest shareholder is an institution, and that firms pay bigger dividends when the largest shareholder, especially an institution, owns a larger percentage of the stock. Furthermore, he discovered that higher institutional (individual) ownership increases (decreases) the likelihood of paying dividends and the amount of a dividend payout (Shahid et al 2016).…”
Section: Ownership Structure and Dividend Policymentioning
confidence: 99%
“…The issues of the relationship of dividends to ownership concentration or the impact of powerful shareholders on dividend payout have not been examined. Some studies, for example, Shahid, Gul, Rizwan, and Bucha (2016) do examine the issue of ownership concentration but adopt a narrow definition of concentration considering only three top shareholders for calculation of ownership concentration. No study, to our knowledge, examines the effect of the presence of large shareholding on dividend policy.…”
Section: Introductionmentioning
confidence: 99%